2024
DOI: 10.1186/s13040-024-00356-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the causal relationship between gut microbiota and cardiovascular diseases: a bidirectional Mendelian randomization analysis

Xiao-Ce Dai,
Yi Yu,
Si-Yu Zhou
et al.

Abstract: Background Previous studies have shown an association between gut microbiota and cardiovascular diseases (CVDs). However, the underlying causal relationship remains unclear. This study aims to elucidate the causal relationship between gut microbiota and CVDs and to explore the pathogenic role of gut microbiota in CVDs. Methods In this two-sample Mendelian randomization study, we used genetic instruments from publicly available genome-wide associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…The results of another MR study evaluating the causal effect of GM on cardioembolic IS support the protective effect of the genus Lachnospiraceae NK4A136 group on IS prognosis in this MR analysis (Dai et al, 2024 ). A previous study reported a significant negative association of the genus L achnospiraceae NK4A136 group with intestinal permeability and the plasma LPS level (Ma et al, 2020 ), which means that genus Lachnospiraceae NK4A136 group is beneficial for protecting the intestinal barrier.…”
Section: Discussionsupporting
confidence: 76%
“…The results of another MR study evaluating the causal effect of GM on cardioembolic IS support the protective effect of the genus Lachnospiraceae NK4A136 group on IS prognosis in this MR analysis (Dai et al, 2024 ). A previous study reported a significant negative association of the genus L achnospiraceae NK4A136 group with intestinal permeability and the plasma LPS level (Ma et al, 2020 ), which means that genus Lachnospiraceae NK4A136 group is beneficial for protecting the intestinal barrier.…”
Section: Discussionsupporting
confidence: 76%